Selma - Moran, Jason 1975- (Studiocanal, 2015)
David Oyelowo stars in this American drama directed by Ava DuVernay. Based on the Selma to Montgomery marches of 1965 that led to the passing of the Voting Rights Act, the film follows the story of James Bevel (Common), Hosea Williams (Wendell Pierce) and Martin Luther King Jr (Oyelowo) as they campaigned for their right to vote. As Luther King Jr led hundreds of like-minded people along the 54-mile highway from Selma to the Alabama state capital of Montgomery, they were met with violent conflict and brutal opposition and had to fight their way through to simply claim what was rightfully theirs. The cast also includes Cuba Gooding Jr, Tom Wilkinson and Oprah Winfrey. The film won an Academy Award and a Golden Globe for Best Original Song
Bildformat 2.40:1 (anamorph)
Orig.: Großbritannien, USA 2014
Enth. 30 Minuten geschnittene Szenen ; Making of (26 Min.) ; Die Entstehung von "Selma" ; Originalaufnahmen aus Selma 1965 ; Musikvideo "Glory" ; Audiokommentare mit Ava DuVernay und David Oyelowo sowie Ava DuVernay, Bradford Young und Spencer Averick
Keywords: King, Martin Luther, -- Jr. -- 1929-1968 -- Drama; King, Martin Luther -- 1929-1968; Geschichte 1965; Civil rights -- Alabama -- Selma -- Drama; Feature films.; Historical films.; Biographical films.; Historischer Film; Schwarze; Biografischer Film; Bürgerrechtsbewegung; Selma, Ala.; USA; DVD-Video